MODIFICATION OF POLY(LACTIC ACID) BY BLENDING WITH POLY(METHYL METHACRYLATE-CO-ETHYL ACRYLATE) FOR EXTRUSION BLOW MOLDING APPLICATION - NAWADON PETCHWATTANA1; PHISUT NAKNAEN; WAROONSIRI JAKRABUTR; JAKKID SANETUNTIKUL; BORWON NARUPAI (Journal of Engineering Science and Technology, 2017)
The current paper investigates the influence of poly(methyl methacrylate-coethyl acrylate) (PMMA-co-EA) content on the flow, mechanical, thermal and morphological properties of poly(lactic acid) (PLA). Mechanical test results indicated that the blends were softer and tougher due to the decreased tensile and flexural strengths and the increased elongation at break and impact resistance. With the presence of PMMA-co-EA, regions of amorphous were found to increase together with the decreased degree of crystallinity at all blend compositions. Rheological properties indicated that molten PLA/PMMA-co-EA blends were more viscous in both under shear and applied load, which suitable for the blow molding process. At 10 wt%, the increased shear viscosity and decreased melt flow index (MFI) were around 240 and 63% respectively. PMMA-co-EA provided good bottle blown product at 10 wt%. Less than this concentration, some flaws were clearly observed.